THE CULTIVATION OF ENTREPRENEURIAL SPIRITS TO THE STUDENTS OF VOCATIONAL HIGHS SCHOOL (SMK) THROUGH SUBJECT OF ISLAMIC RELIGIOUS EDUCATION AND ETHICS - Arif Cahya Wicaksana; Sukiman Sukiman (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2018)
One important aspect that is needed in the face of the current industrial 4.0 era is how to interest entrepreneurs can thrive, especially in the younger generation. Vocational High School (SMK) as an educational institution is a very strategic place to instill entrepreneurial spirit. Planting the spirit of entrepreneurship to be more effective must be done through all subjects. The subjects of Islamic Religious Education (PAI) and Ethics (Budi Pekerti) are one of the compulsory subjects in Vocational School and should also contribute to instilling the entrepreneurial spirit. The form of contribution from Islamic Religious Education is in the way of non-technical skills that are strictly related to attitudes and behavior or character that must be possessed by an entrepreneur or in other words Islamic Religious Education contributes to instilling the spirit or spirit of entrepreneurial spirit in students. The cultivation of entrepreneurial spirit is not necessary by adding new material but can be integrated with PAI and Ethics learning material that already exists in the curriculum. The PAI teachers are an essential and central component in determining success in integrating PAI and Ethics character subjects with the entrepreneurial world. Therefore, the PAI teachers need to have adequate insight into entrepreneurship and create a conducive learning atmosphere to instill an entrepreneurial spirit in students.